Catalytic Asymmetric Reactions of Ketimines and Alkenes via [2 + 2] Cycloaddition: Chemical Reactivity Controlled by Switching a Heteroatom - Zhao, Qun; Li, Yao; Ren, Zhiyuan; Shao, Ying-Bo; Chen, Li; Li, Xin (Journal of the American Chemical Society, 2024)
Azetidine units are commonly found in natural products and biologically active drugs. The [2 + 2] cycloaddition of imines and alkenes has been extensively used in the synthesis of such structures, while enantioselective approaches remain elusive. Herein, an efficient B(C6F5)3/chiral phosphoric acid-catalyzed asymmetric [2 + 2] cycloaddition of ketimines and aryl vinyl selenides was presented, delivering valuable chiral azetidines with excellent stereoselectivities (>20:1 dr and up to 96:4 er). What’s even more interesting was that when a “Se” atom was switched to an “S” atom, the reaction proceeded through a [2 + 2] cycloaddition/ring-opening cascade process, affording a range of chiral thioacetals with high enantioselectivities (up to 98:2 er), which were also important organic sulfur compounds. Mechanistic experiments, coupled with density functional theory (DFT) calculations, shed light on a mechanism involving stepwise [2 + 2] cycloaddition and ring-opening processes, with the initial alkenylation step identified as crucial for achieving stereoselective control.